2021
DOI: 10.1021/acscatal.1c03571
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation of Hydrazine Utilizing High-Entropy Alloys: Assisting the Oxygen Evolution Reaction at the Thermodynamic Voltage

Abstract: Hydrazine electrooxidation is an important reaction as it assists in decreasing the OER overvoltage. Herein, we report the utilization of a high-entropy nanocatalyst alloy for the electrooxidation of hydrazine. The high-entropy nanocatalyst comprising five elements (Ag, Au, Pt, Pd, Cu) shows profound activity toward this molecule at a low overvoltage. An intriguingly high-entropy nanocatalyst prepared by the casting-cum-cryomilling method is endowed with the unique catalytic activity for the HzOR. A detailed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Since most syntheses of HEAs have been based on melts at high temperatures, it has been challenging to obtain nanosized products with high specific surface areas. Additional steps such as cryomilling or de-alloying have been used to address the chal- lenge, 24,27,29,35,37,47,50 but they come at the price of limited control of the final product, limited crystallinity, and high production losses. Physical vapor deposition methods and carbothermal shock synthesis have been employed successfully, 22,23,52−56 but these synthesis techniques are restrictive in their substrate applicability and productivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since most syntheses of HEAs have been based on melts at high temperatures, it has been challenging to obtain nanosized products with high specific surface areas. Additional steps such as cryomilling or de-alloying have been used to address the chal- lenge, 24,27,29,35,37,47,50 but they come at the price of limited control of the final product, limited crystallinity, and high production losses. Physical vapor deposition methods and carbothermal shock synthesis have been employed successfully, 22,23,52−56 but these synthesis techniques are restrictive in their substrate applicability and productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned assets make HEAs obvious candidates for energy technology such as proton-exchange membrane electrolysis and alcohol fuel cells, which are likely focal points of future power-to-X technology. The usage of HEAs for electrocatalysis has been investigated theoretically, and promising experimental results have already been reported for the oxygen reduction reaction (ORR), hydrogen evolution reaction (HER), oxygen evolution reaction (OER), hydrogen oxidation reaction (HOR), CO 2 reduction, methanol/ethanol oxidation, urea oxidation, glycerol oxidation, and combinations of these. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…–1 ) with a (in Å) validated with literature data. HEAs (FCC) a (FCC) (BCC) a (BCC) Lowest Predicted phase References PtPdFeCoNi −2.6973 3.6713 −2.4330 2.9140 −2.6973 FCC FCC 26 , 36 a = 3.73 36 PtPdFeCoIr −2.6859 3.7440 −2.376 2.9715 −2.6859 FCC FCC 37 PtPdFeRhIr 0.2036 3.8130 0.4338 3.0264 0.2036 FCC FCC 38 a = 3.834 38 PtPdCoNiCu −2.6009 3.6831 −2.3553 2.9233 −2.6009 FCC FCC 39 PtPdCuAgAu 0.0882 3.9351 0.1317 3.1233 0.0882 FCC FCC 7 , 8 , 33 a = 3.936 7 ...…”
Section: Resultsmentioning
confidence: 99%
“…As in the aspect of the use of HEA as catalytic materials, the PtPd-based HEAs are among high potential candidates that can be utilized in CO 2 and CO reduction reaction 7 , 8 , oxygen evolution reaction 33 , oxygen reduction reaction 34 , and hydrogen evolution reaction 35 . However, from the literature, it was found that most experimental works involving PtPd-based HEAs focused mainly on the report of limited formulae of HEA in terms of novel synthesis and characterization techniques 26 , 36 43 .…”
Section: Introductionmentioning
confidence: 99%